Nanotheranostics against COVID-19: From multivalent to immune-targeted materials (2020)
Destructive impacts of COVID-19 pandemic worldwide necessitates taking more appropriate measures for mitigating virus spread and development of the effective theranostic agents. In general, high heterogeneity of viruses is a major challenging issue towards the development of effective antiviral agents. Regarding the coronavirus, its high mutation rates can negatively affect virus detection process or the efficiency of drugs and vaccines in development or induce drug resistance. Bioengineered nanomaterials with suitable physicochemical characteristics for sitespecific therapeutic delivery, highly-sensitive nanobiosensors for detection of very low virus concentration, and real-time protections using the nanorobots can provide roadmaps towards the imminent breakthroughs in theranostics of a variety of diseases including the COVID-19. Besides revolutionizing the classical disinfection procedures, state-of-the-art nanotechnologybased approaches enable providing the analytical tools for accelerated monitoring of coronavirus and associated biomarkers or drug delivery towards the pulmonary system or other affected organs. Multivalent nanomaterials capable of interaction with multivalent pathogens including the viruses could be suitable candidates for viral detection and prevention of further infections. Besides the inactivation or destruction of the virus, functionalized nanoparticles capable of modulating patient’s immune response might be of great significance for attenuating the exaggerated inflammatory reactions or development of the effective nanovaccines and medications against the virus pandemics including the COVID-19.